Port-railway connection in Setúbal (Portugal) – an understanding of the past for a sustainable future. - Lourencetti, Fernanda de Lima (2022)
This article aims to analyse the process of connecting the railway and the port of Setúbal within the development of sustainable urban policies. Since the nineteenth century, cities have faced challenges concerning the logistics of transportation. The urban specificities of port cities attracted the attention of experts in the mid-twentieth century, after some cities had relocated or restructured their port areas. Consequently, by the end of the twentieth century, intermodality became a fundamental tool to guarantee a sustainable urban plan. Currently, the sustainability paradigm has increased the concerns about port cities, due to their environmental, social, and economic qualities. This article aims to explore the historical relationship between the railway and the port of Setúbal. Focus is placed on the attempts to develop an intermodal system in Setúbal, while confronting it with its urban development. By discussing the restructuring process of the port of Setúbal since the arrival of the railway, this paper provides an overview of the interests and actors involved in the connection between these infrastructures. The historical analysis of the port-rail infrastructure reveals the urgency of this kind of understanding for current and future sustainable urban planning.